Treatment of systemic mastocytosis with interferon-γ: failure after appearance of anti-IFN-γ antibodies - Fiehn, Christoph; Prümmer, O.; Gallati, H.; Heilig, Bernhard; Hunstein, Werner (European journal of clinical investigation, 1995)
Abstract. We report a case of a patient with systemic mastocytosis who was treated with interferon-γ. Because of severe diarrhoea, nausea and weight loss due to mast cell infiltration of the gastric mucosa the patient received 150μg d-1 interferon-γ subcutan-eously for 10 months. During therapy, the plasma concentrations of IL-3, IL-4 and GM-CSF, which seem to play a role in mast cell growth and differentiation were monitored. The patient had good symptomatic relief and the initially very high eosinophil counts in the pripheral blood showed a partial reduction. However, after 4 months of therapy the patient relapsed. In serum obtained after the relapse, but not in stored serum from the beginning of the therapy, neutralizing antibodies against interferon-γ were found. Therefore an initial response to the therapy and a secondary failure mediated by treatment-induced antibodies against recombinant interferon-γ might be suggested. Interferon-γ may be a well tolerated therapeutic option in systemic mastocytosis. However, treatment-induced neutralizing antibodies against recombinant interferon-γ should be considered if secondary treatment failure occurs.